Investigação exploratória dos fatores genéticos associados ao sistema de determinação sexual em Arapaima gigas (Pirarucu) - Cavalcante, Renata Lilian Dantas (2020)
The Pirarucu, (Arapaima gigas) is one of the largest freshwater bony fish in the world, with adults that can weigh 200 kilograms and measure 3 meters in length. It belongs to the Arapaimidae family, of the Osteoglossiformes order and has the Amazon Basin as its natural habitat. Due to its large size and its low fat containing and low fishbone, Arapaima gigas has quickly become a species of special interest in fish-farming. A problem related to its fishery exploitation is that the genetic mechanisms that control the sexual differentiation in Arapaima gigas are not known. The sexual maturation in Arapaima gigas occurs belatedly, around the third to fifth year of life, and sexual dimorphism is not a strong characteristic of the species. For more sustainable management, it is of paramount importance to seek an effective and non-invasive method to sexually differentiate juvenile individuals of Arapaima gigas. For this, the establishment of a molecular genetic marker related to sexual differentiation would be an advantageous tool. Previous analyses of the Arapaima gigas genome could not find statistically significant determining large genomic regions that are associated with the sex-determination system of these individuals. In this study, we proposed to make uncommon Bioinformatic approaches, that is not so usual, for the identification of genomic differences between individuals of the opposite sex, with the intention of identifying repetitive regions in excess or scarcity in one sex. For this purpose, we used genomic data from six adult representatives of Arapaima gigas, three males and three females, in addition to the reference genome of Pirarucu ID: 12404 deposited in NCBI. After these exploratory studies in the genome, we noticed the existence of k-mers that are represented differently among individuals of the opposite sex. We also identified 22 scaffolds containing haploidy in one sex and with the antagonistic scenario (absence of haploidy) in the other one. Additionally, we performed the identification of the microsatellite panel in Arapaima gigas was performed, where 95.485 microsatellites were found. The knowledge of these microsatellite regions is very important for the continuation of this work, as it enables their use as molecular markers of genomic regions, which would facilitate experimental techniques of isolation of sequences of interest, especially when associated with the portions of haploidy existing in only one of the sexes of Arapaima gigas would facilitate experimental techniques of isolation of sequences of interest. The different proportions in the count of k-mers and heterozygous sites (haploidy) can indicate the existence of genetic factors, which if proven through experiments on the bench, can aid in the sexing of Arapaima gigas individuals.